2010
DOI: 10.1016/j.yjmcc.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic network restructuring integral to the energetics of embryonic stem cell cardiac differentiation

Abstract: Decoding of the bioenergetic signature underlying embryonic stem cell cardiac differentiation has revealed a mandatory transformation of the metabolic infrastructure with prominent mitochondrial network expansion, and a distinctive switch from glycolysis to oxidative phosphorylation. Here, we demonstrate that despite reduction in total glycolytic capacity, stem cell cardiogenesis engages a significant transcriptome, proteome, as well as enzymatic and topological rearrangement in the proximal, medial, and dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 65 publications
8
139
0
2
Order By: Relevance
“…Embryonic heart development is a tightly regulated process for which the energy source has been found to be a key determinant. During early development, cardiomyocyte precursors rely mainly on glycolysis to obtain energy (Chung et al 2007(Chung et al , 2010. In addition, it has been described that proper heart formation is the result of a combination of genetic and mechanical factors that result in the proper development of the cardiac structures (Hove et al 2003, Vermot et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic heart development is a tightly regulated process for which the energy source has been found to be a key determinant. During early development, cardiomyocyte precursors rely mainly on glycolysis to obtain energy (Chung et al 2007(Chung et al , 2010. In addition, it has been described that proper heart formation is the result of a combination of genetic and mechanical factors that result in the proper development of the cardiac structures (Hove et al 2003, Vermot et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PSCs contain fewer and more immature mitochondria with globular shape, poorly developed cristae, and perinuclear localization as compared with the adult differentiated cell types containing a high number of well-developed and elongated or branched mitochondria. 24,25 Consistently, the voltage difference (ΔΨ) across the mitochondrial inner membrane because of the proton gradient 2,3 (http://www.biocarta.com/pathfiles/h_etcPathway.asp) is significantly lower in the mitochondria of PSCs compared with differentiated cells. [25][26][27][28][29] Differentiation of PSCs into somatic cells is accompanied by a shift from cytosolic glycolysis to mitochondrial respiration.…”
Section: Metabolic Pathways Involved In the Energetics Of Psc Pluripomentioning
confidence: 98%
“…For example, there is evidence that alterations in energy generation over this period may be related to loss of "stemness" in cardiomyocytes [8,34].…”
Section: Neonatal Cardiac Mitosis and Regenerationmentioning
confidence: 99%
“…To support the resultant increased cardiac energy requirement, the heart shifts from energy generation via glycolysis in the fetal heart to predominant oxidative-phosphorylation of lipid in the postnatal heart [7][8][9], accompanied by a decrease in the amount of stored glycogen in the heart after birth [10]. A number of parallel physiological events are thought to underlie this process.…”
Section: Introductionmentioning
confidence: 99%